Parametric Study of the Effect of the Suspension Composition on the Electrophoretic Deposition of Alumina (Journal of University of Babylon for Engineering Sciences, 2018)
Electrophoretic deposition (EDP) is gaining increasing attention both in science and industry because this method has allowed the formation of thin films or multilayer films of controlled thickness and morphology. The method enables the formation of films on substrates of complex geometry that suits for various applications.This work is a study the effect of polyethylene glycol as a binder-suspension agent, the amount the solid loading (alumina particles), and the effect of the toluene as a dielectric liquid, on the pH of suspension, the final thickness and green density of the deposed parts.It has been shown that a certain amount of polyethylene glycol when added to ethanol or ethanol-30%toluene has given good results for both the green density and the thickness.